The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.9788/tp2016.2-14en
|View full text |Cite
|
Sign up to set email alerts
|

Nature and Children’s Play: Investigation of Child-Nature Interaction in Urban Green Parks

Abstract: Studies have shown that contact with nature brings cognitive, social, physical and psychological benefi ts to children, infl uencing their development. In natural environments, children play jumping, running, digging, building, hiding, climbing trees, and develop the capacity of imagination in make-believe play. In the present study, which aimed to understand the child-nature interaction in play, 30 children aged 2 to 10 years were observed in two urban green parks of Florianópolis, southern Brazil (SC). Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(27 reference statements)
0
2
0
3
Order By: Relevance
“…Raymundo, Kuhnen, and Soares (2010) and Kuh et al (2013) observed playgrounds where sand has been identified as a preferred element for performing constructive play by preschoolers. Machado et al (2016) also observed that sand was the most common element used in constructive play for children in one urban green park where this resource was part of the native ecossystem. According to Tuan (1978), such children´s attraction to this natural resource is related to the imagination and sense of destruction that can be exercised in building structures.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Raymundo, Kuhnen, and Soares (2010) and Kuh et al (2013) observed playgrounds where sand has been identified as a preferred element for performing constructive play by preschoolers. Machado et al (2016) also observed that sand was the most common element used in constructive play for children in one urban green park where this resource was part of the native ecossystem. According to Tuan (1978), such children´s attraction to this natural resource is related to the imagination and sense of destruction that can be exercised in building structures.…”
Section: Discussionmentioning
confidence: 95%
“…Tanto Raymundo, Kuhnen, y Soares (2010) como Kuh et al (2013) observaron parques en los que se identificó la arena como el elemento preferido de los preescolares para realizar juegos constructivos. Machado et al (2016) también observó que la arena era el elemento utilizado más habitualmente en los juegos constructivos de los niños en un espacio verde urbano en el que este recurso era parte del ecosistema local. Según Tuan (1978), la atracción de los niños por este recurso natural está relacionada con la imaginación y la sensación de destrucción que pueden realizar en las estructuras en construcción.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Pada saat anak bermain konstruktif anak juga belajar menghibur diri, bersikap sosial, bekerjasama dan menghargai prestasi teman bermainnya. (Machado et al, 2016) mengemukakan bahwa bermain konstruktif bertujuan untuk untuk menciptakan sesuatu objek menjadi bentuk yang sudah direncanakan. Bermain konstruktif didesain melalui permainan yang terjadi ketika anak-anak Agar anak memahami bagaimana mengkonstruksi atau membangun bentuk yang dikehendaki seperti apa yang pernah dilihatnya.…”
Section: Pendahuluanunclassified